A review on material extrusion additive manufacturing of polycarbonate‐based blends and composites: Process‐structure–property relationships - Nima Rashidi Mehrabadi; Gholamreza Pircheraghi; Ali Ghasemkhani; Parsa Hosseinpour Sanati; Alireza Shahidizadeh; Alireza Kaviani; Suprakas Sinha Ray (SPE Polymers)
Abstract Polycarbonate (PC) is a valuable engineering polymer with numerous technical characteristics like desirable mechanical properties, high heat resistance, chemical resistance, optical clarity, and electrical insulation capabilities. Therefore, it finds extensive use in aerospace, automotive, consumer goods, optics, medical devices, and electronics. Materials extrusion additive manufacturing offers several advantages, such as customized geometry, minimal material waste, cost‐effectiveness, and ease of material modification. Accordingly, PC has recently emerged as a robust and durable additive manufacturing material. This review aims to investigate how printing parameters in materials extrusion additive manufacturing affect the properties of PC and PC‐based materials, with a specific emphasis on mechanical properties. The main drawbacks associated with pure PC filaments, like high print temperatures, warping tendencies, and a propensity to retract during printing, are also discussed. Considering the significant demand for developing PC blends and composites tailored for application in material‐extrusion additive manufacturing, the influence of different types of fillers, including polymeric, metallic, and ceramic, on improving the mechanical behavior is then reviewed. This paper explores the diverse applications of additively manufactured PC parts, especially within advanced areas like aerospace, electrical engineering, and medicine. Lastly, prospects and challenges are presented in the review. Highlights PC is a key engineering polymer for extrusion 3D printing. Printing parameters affect the quality and strength of polycarbonate parts. Various fillers adjust polycarbonate‐based composites' mechanical properties. High temperatures, warping, and retraction are major 3D printing challenges. 3D‐printed PC composites can be used in a variety of applications.